KEBIJAKAN WAWASAN KEBANGSAAN DAN PENANGANAN KONFLIK SOSIAL DALAM PRESPEKTIF COLLABORATIVE GOVERNANCE DI KABUPATEN PANDEGLANG - Rusdjiman Soemaatmadja; Tjahya Supriatna; Hyronimus Rowa; Kusworo (GoAcademica Research dan Publishing, 2020)
Paying attention to the development of the life of the nation and state which is experiencing turmoil with the existence of conflicts with a racial background, separatism, radicalism and terrorism which occur if traced have a relationship with Pandeglang Regency related to its population. This is also shown by the high data on conflicts that occurred in Pandeglang Regency among Regencies / Cities in Banten Province. This research uses a qualitative approach, so that in interpreting the conditions of the actors, it is more developed with a triangulation analysis tool. The results of this study found that the implementation of the national insight policy is still not going well collaboratively, causing many social problems in society caused by human resources and budget factors.